2015
DOI: 10.7324/japs.2015.50715
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, in vitro Characterization and Stability Studies of Fast Dispersing Tablets of Diclofenac Sodium

Abstract: The present study was aimed to formulate, develop and evaluate the fast dissolving tablets of diclofenac sodium, used for the treatment of arthritis, inflammation, pain. Fast dissolving tablets of diclofenac sodium were prepared by direct compression method using crospovidone and sodium starch glycolate as superdisintegrants in concentrations of 5.3%, 6.6% and 8% w/w and in combination. In this work microcrystalline cellulose and mannitol are investigated as diluents. Prepared powder mixtures were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…COOH groups of DS indicate stretching vibrations at 3310 cm −1 , while peaks at 3430 cm −1 and 1654 cm −1 characterize the stretching vibrations of N–H and C=C, respectively. Swain et al (2015) reported the same peaks in their studies, which further support our studies [ 21 ]. The FTIR spectrum of SA ( Figure 2 B) indicates an extensive band at 3420 cm −1 due to OH groups of hydrogen bonding.…”
Section: Resultssupporting
confidence: 92%
“…COOH groups of DS indicate stretching vibrations at 3310 cm −1 , while peaks at 3430 cm −1 and 1654 cm −1 characterize the stretching vibrations of N–H and C=C, respectively. Swain et al (2015) reported the same peaks in their studies, which further support our studies [ 21 ]. The FTIR spectrum of SA ( Figure 2 B) indicates an extensive band at 3420 cm −1 due to OH groups of hydrogen bonding.…”
Section: Resultssupporting
confidence: 92%
“…FTIR spectrum of DS ( Figure 2 A) indicates COOH-stretching vibrations at the peak 3340 cm −1 , while at peaks 1650 and 3480 cm −1 , C=C and N–H stretching are observed, correspondingly [ 24 ]. Swain et al (2015) reported the above peaks in his studies in the same range as in our studies [ 25 ].…”
Section: Resultssupporting
confidence: 88%
“…The presence of carboxyl group is confirmed by the overlapping of two different functional groups, i.e., -OH and C-O at 1430 cm −1 and 1387 cm 1 respectively. Likewise, S=O stretching vibration of the sulfate group is detected at peak 1250 cm −1 [48,49]. Similarly, CBP FTIR spectra (Figure 5C) reveal stretching vibration of C=O, OH, and R-CH 2 at 1632, 2703, and 2998 cm −1 , respectively [50][51][52].…”
Section: Measurement Of Ftirmentioning
confidence: 94%